Dynamic induction of the myelin‐associated growth inhibitor Nogo‐A in perilesional plasticity regions after human spinal cord injury. (13th June 2022) - Schwaiger, Carmen; Haider, Thomas; Endmayr, Verena; Zrzavy, Tobias; Gruber, Victoria E.; Ricken, Gerda; Simonovska, Anika; Hametner, Simon; Schwab, Jan M.; Höftberger, Romana
Abstract: The myelin‐associated inhibitor Nogo‐A (Reticulon 4, RTN4) restricts axonal outgrowth, plasticity, and neural circuitry formation in experimental models of spinal cord injury (SCI) and is targeted in clinical interventions starting treatment within 4 weeks post‐SCI. Specifically, Nogo‐A expressed by oligodendroglia restricts compensatory neurite sprouting. To interrogate the hypothesis of an inducible, lesion reactive Nogo‐A expression over time, we analyzed the spatiotemporal Nogo‐A expression at the spinal lesion core (region of tissue necrosis and axonal damage/pruning) and perilesional rim (region of plasticity formation). Spinal cord specimens of SCI subjects ( n = 22) were compared to neuropathologically unaltered controls ( n = 9). Nogo‐A expression was investigated ranging from acute (0–3 days), early subacute (4–21 days), late subacute (22–90 days) to early chronic–chronic (91 days to 1.5 years after SCI) stages after SCI. Nogo‐A expression in controls is confined to motoneurons in the anterior horn and to oligodendrocytes in gray and white matter. After SCI, the number of Nogo‐A + and TPPP/p25 + oligodendrocytes (i) inclined at the organizing perilesional rim specifically, (ii) increased further over time, and (iii) peaked at chronic stages after SCI. By contrast, at the lesion core, the number of Nogo‐A + and TPPP/p25 + oligodendrocytes did not increase. Increasing numbers of Nogo‐A + oligodendrocytes coincided with oligodendrogenesis corroborated by Nogo‐A coexpression of Ki67 +, TPPP/p25 + proliferating oligodendrocytes. Nogo‐A oligodendrocyte expression emerges at perilesional (plasticity) regions over time and suggests an extended therapeutical window for anti‐Nogo‐A pathway targeting interventions beyond 4 weeks in patients after SCI. Abstract : Nogo‐A oligodendrocytes expression emerges at perilesional regions over time and suggests an extended therapeutical window for anti‐Nogo‐A pathway trageting interventrions beyond four weeks in patients after spinal cord injury.